Perancangan Compact Furnitur untuk Penghuni Rumah Susun di Surabaya - Bertaria Alvionita; Adi Santosa; Anik Rakhmawati (Intra, 2016)
One of the government's effort concerning healthy living and healthy is by developing flat house for the community. To support resident's activities, each of the resident need to do a good spatial planning. These planning could be supported by selecting efficient storage so that the goods owned can be arranged neatly and easy to find. Storage selection also serves to avoid the intended room look cramped and unclean. ―The Simplicity of Compact‖ is the concept shown on this design paper. The appropriate storage system for flat house is called compact furniture, in which there will be some furniture put into 1 furnishing. Compact on the design is meant for both of storage terms and also the shape of the furniture. It is intended that once the furniture used, it can be immediately be stored back into the furnishings. The purpose will be to make the room more spacious, because not many items scattered around. The design applied to the furnishing also using a modular system which meant that it can be purchased separately (installment) according to the user needs. Furniture's simplicity is applied for color, material, finishing and construction used to design the furniture. Furnishing with compact systems design is suitable for the ever modest flat house. As the design’s purpose is to make the room looked more spacious, cleaner and importantly it is designed for flat house residents to take out the intended furniture when needed.